2012
DOI: 10.1590/s1676-06032012000400002
|View full text |Cite
|
Sign up to set email alerts
|

Folk taxonomy of fishes of artisanal fishermen of Ilhabela (São Paulo/Brazil)

Abstract: This article investigates the folk taxonomy of four artisanal fisheries communities in Ilhabela/SP. The local folk taxonomy shows how these fishermen identify, name and classify fish resources in the environment exploited by them. Forty-two fishermen from four different local communities of Ilhabela were interviewed through a structured questionnaire and photographs of fish species with occurrence for the southeast region of Brazil. Respondents identified the 24 species listed as 50 generic names and 27 binomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
2
13
0
3
Order By: Relevance
“…Local names given to fish by the inhabitants of fishing communities are generally very similar, and have been reported in other localities in Brazil (Begossi and Figueiredo 1995;Freire and Pauly 2005;Previero et al 2013;Ramires et al 2012), suggesting a geographic continuity in terms of popular names along the Brazilian coast, although the similarity between the fish names used in Tamandaré and Batoque is less than 40%. Different names are given to the same species even in a single community (and, as expected, between distinct communities), demonstrating the vocabulary richness of these societies.…”
Section: Discussionsupporting
confidence: 66%
“…Local names given to fish by the inhabitants of fishing communities are generally very similar, and have been reported in other localities in Brazil (Begossi and Figueiredo 1995;Freire and Pauly 2005;Previero et al 2013;Ramires et al 2012), suggesting a geographic continuity in terms of popular names along the Brazilian coast, although the similarity between the fish names used in Tamandaré and Batoque is less than 40%. Different names are given to the same species even in a single community (and, as expected, between distinct communities), demonstrating the vocabulary richness of these societies.…”
Section: Discussionsupporting
confidence: 66%
“…Studies conducted with artisanal fishers along the Brazilian coast have demonstrated through fish nomenclature analyses and the types of relationships that different folk taxa represent to local communities by generic and specific terminologies [ 15 , 20 ]. In addition, folk classification has shown its potential to support scientific research especially when data is limited and to contribute to fisheries decision-making [ 15 , 20 , 21 ]. Nevertheless, the use of ethnotaxonomy to understand shark uses and promote their management is still incipient globally and in Brazil, possibly due to their relatively lower participation on global catches scenarios compared to target fishing groups [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, many researchers have recognized and used TEK for various purposes, such as studies on fisheries assessment (Neis et al, 1999;Bender et al, 2013), taxonomy of marine organisms (Berlin, 1992;Drew, 2005;Ramires et al, 2012), fish spawning aggregation (Robinson et al, 2004;Samoilys et al, 2006;Hamilton et al, 2011), and design of conservation and fisheries management measures (Friedlander et al, 2003;Drew, 2005;Baird, 2007;McClanahan et al, 2009;Masalu et al, 2010). Furthermore, several studies have focused on the differences between fishers' TEK and CSK, while recognizing the complementarity between these two knowledge systems in the management and conservation of aquatic ecosystems (García-Allut et al, 2007;Johannes and Neis, 2007;Jackson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%